HUBUNGAN USIA, MASA KERJA, WAKTU KERJA, SIKAP KERJA DAN AKTIVITAS PEKERJAAN DENGAN KEJADIAN NYERI PUNGGUNG BAWAH PADA PETANI PADI DESA SEMEN - Nurcahyani, Ari Dwi; Ekawati, Ekawati; Jayanti, Siswi (Jurnal Kesehatan Masyarakat, 2024)
Indonesia is an agrarian country so that agriculture is one of the sectors with the largest number of workers. Agriculture is an informal sector job that still uses a lot of manual handling methods so that it has the potential to cause complaints of low back pain. Low back pain is a health problem in the form of acute pain that is felt in the lower back (lumbosacral) area in the form of local or radicular pain. Risk factors for low back pain include individual factors, occupational factors and environmental factors. This research is a quantitative-research with analytic observational method and cross-sectional approach. The population is farmers from of Semen village and registered on rukun tani group. The sample is 30 people using total sampling. Independent variables is age, working period, working time, work attitudes and work activities with dependent variable Low Back Pain. Data collection techniques used individual characteristic questionnaires, nordic body map, VAS scale and OWAS method. Data analysis technique uses Fisher’s Exact Test statistical test. The results showed a greater distribution of independent variables age > 35 years, work experience > 5 years, work attitudes requiring improvement, and heavy work activities. The results of the bivariate analysis showed that there was a significant relationship between age (p-value = 0.035), working period (p-value = 0.002) and working time (p-value = 0.004) with complaints of low back pain in rice farmers in hamlet X Semen Village as evidenced by p-value <0.05. Keywords: Low Back Pain, Rice Farmes, VAS scale, OWAS method.